math
posted by alex .
x+5y= 3
3x2y= 8
sovle using substituion

(1) x + 5y = 3
(2) 3x  2y = 8
substitution method: we first choose one of the equation, and express one of the variables in terms of the other variable,, here let's choose equation (1), and express x in terms of y:
x + 5y = 3
x = 3  5y
now, we substitute this to equation (2), and we solve for y:
3x  2y = 8
3(3  5y)  2y = 8
9  15y 2y = 8
17y = 17
y = 1
substituting this back to either equations to get x (let's choose (1)):
x = 3  5y
x = 3 5(1)
x = 3 + 5
x = 2
hope this helps~ :)